A cross sectional study to determine the correlation of blood glucose and HbA1C in type 2 diabetes mellitus patients - Baishya, Reeta; Bora, Madhurima; Mazumdar, Arijit (International Journal of Research in Medical Sciences, 2023)
Background: Measurement of glycosylated hemoglobin (HbA1c) is considered the gold standard for monitoring chronic glycemic level of diabetes patients. HbA1c is a form of hemoglobin that is measured primarily to identify the average plasma glucose concentration over prolonged periods of time. Levels of HbA1C represent the average blood glucose levels of diabetic patients over the previous 120 days. The objective of this study was to see the correlation between HbA1c levels and glucose levels. Methods: This cross-sectional study included 60 randomly selected subjects with known diabetes. Both fasting and post prandial blood glucose levels were measured by using venous blood samples. HbA1c levels were measured in venous blood by immunoturbidimetric method. Data were recorded on a proforma in MS-excel sheet. Pearson’s coefficient of correlation was applied to find out any significant correlation between the HbA1c levels and the both fasting and postprandial blood glucose levels. Results: Results were obtained by statistical calculation and plotted with respect to scatter and bar diagram was done and a p<0.05 was considered significant (With 95% CI). Conclusions: A significant linear positive correlation exists between levels of HbA1C and fasting and post prandial blood glucose.